Regional Dimension of Malaysiaâs Foreign Policy during the Cold War, 1957-1989: A Historical Evaluation - Tajari, Arvin (SUSURGALUR, 2014)
ABSTRACT: Malaysia, like other countries in the world, has formulated her foreign policy to achieve her national interests. Foreign policy of Malaysia has been developed since the independent, and regional dimension played an important role in shaping Malaysiaâs foreign policy. This article examines Malaysiaâs foreign policy since the independent from the regional perspective. It is understood that Malaysiaâs foreign policy is very much shaped from the Southeast Asia region, in particular ASEAN (Association of South East Asia Nations) itself. Since the independent, Southeast Asia becomes one of the major concerns in Malaysiaâs foreign policy, where the region experienced major event happened directly and indirectly influenced foreign policy of the countries in Southeast Asia. In fact, regional dimension has shaped Malaysiaâs foreign policy from the beginning of the independent. The study, firstly, evaluate on historical background on Malaysiaâs foreign policy since the first Prime Minister, Tunku Abdul Rahman, until Dr. Mahathir Mohamad. Secondly, the study seeks to highlight main issues, orientation, and changes in Malaysiaâs foreign policy by examining the different administration. Thirdly, the article seeks to look the importance of Malaysiaâs foreign policy within the regional aspect. KEY WORD: Malaysiaâs foreign policy, national interests, the roles of prime ministers, regional cooperation, security, and economic development.IKHTISAR: Artikel ini bertajuk âDimensi Serantau dalam Dasar Luar Malaysia semasa Perang Dingin, 1957-1989: Satu Penilaian Sejarahâ. Malaysia, seperti negara-negara lain di dunia, telah merumuskan dasar luar untuk mencapai kepentingan negara berkenaan. Dasar luar Malaysia telah dibangunkan sejak merdeka, dan dimensi serantau memainkan peranan yang penting dalam membentuk dasar luarnya. Artikel ini mengkaji dasar luar Malaysia sejak merdeka dari perspektif serantau. Difahamkan bahawa dasar luar Malaysia adalah sangat direka-bentuk oleh rantau Asia Tenggara, khususnya ASEAN (Persatuan Bangsa-bangsa Asia Tenggara) itu sendiri. Sejak merdeka, Asia Tenggara menjadi salah satu kebimbangan utama dalam dasar luar Malaysia, dimana rantau ini mengalami peristiwa besar yang berlaku secara langsung dan tidak langsung mempengaruhi dasar luar negara-negara di Asia Tenggara. Malah, dimensi serantau telah membentuk dasar luar Malaysia dari permulaan kemerdekaan. Kajian ini, pertamanya, menilai tentang latar belakang sejarah dasar luar negara Malaysia sejak Perdana Menteri pertama, Tunku Abdul Rahman, sehingga Dr. Mahathir Mohamad. Keduanya, kajian ini bertujuan untuk mengetengahkan isu-isu utama, orientasi, dan perubahan dalam dasar luar Malaysia dengan memeriksa pentadbiran yang berbeza. Ketiganya, artikel ini bertujuan untuk melihat kepentingan dasar luar Malaysia dalam aspek serantau.KATA KUNCI: Dasar luar Malaysia, kepentingan negara, peranan perdana menteri, kerjasama serantau, keselamatan, dan pembangunan ekonomi.About the Author: Arvin Tajari is a Lecturer at the Faculty of Social Science and Liberal Art UCSI (University College Sedaya International), No.1, Jalan Menara Gading, UCSI Heights, Cheras 56000, Kuala Lumpur, Malaysia. Â He is also as Ph.D. Candidate for Security and International Relations at the School of History, Politic, and Strategy UKM (National University of Malaysia). His e-mail address is arvintajari@gmail.comÂ Â How to cite this article? Tajari, Arvin. (2014). âRegional Dimension of Malaysiaâs Foreign Policy during the Cold War, 1957-1989: A Historical Evaluationâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(1), Maret, pp.81-90. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808, ISSN 2302-5808. Chronicle of the article: Accepted (January 12, 2014); Revised (February 15, 2014); and Published (Maret 24, 2014).